24. Dnevi varstvoslovja, Podčetrtek, 13. in 14. junij 2023: Zbornik povzetkov (University of Maribor Press, 2023)
24th Days of Criminal Justice and Security, Podčetrtek, 13th & 14th of June 2023: Book of Abstracts. Contributions of the 24th Conference Days of Criminal Justice and Security represent professional and scientific consideration of paths and resources for provision of security in contemporary society. The book of abstracts includes abstracts of five round tables and forty-eight contributions, dealing with a broad range of topics such as policing, private security, complaint procedures, security and safety in local communities, criminal investigation, criminology, violence, private detective activities, the implementation of criminal sanctions, cyber security, technologies in the security provision, and other current security challenges of contemporary society.